Feminization of poverty program on female breadwinners in East Java, Indonesia - Doddy Sumbodo Singgih; Sudarso Sudarso; Siti Mas'udah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2020)
This article describes the feminization of poverty-reducing program by directing the program to female breadwinners in 10 regencies in East Java Province, Indonesia. The main activity of such program is to provide productive financial support to a target group, namely poor female breadwinners in rural areas. The main focus of the research is to examine the targeting accuracy of the program in providing productive financial support to the target group. To acquire this objective, a survey was conducted to collect data for the examination. In addition, the targeting accuracy is measured for the accuracy of its recipients, its amount, and its utilization. The results of the study indicate that the feminization of poverty-reducing program has met the target. It means that the funds have really been given to the poor female breadwinners who live in rural areas. The sum of the money has been in agreement with the amount that should be given, and it has been utilized by the target group productively in accordance with the program objectives.